PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI PENGGAJIAN DAN PENGUPAHAN TERHADAP EFEKTIFITAS KINERJA PERUSAHAAN PADA PT BPR TUNAS ARTHA JAYA ABADI NGANJUK - DWI PUJI RAHAYU (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2016)
Payroll accounting information system and wage a series of recurring business activities and related data processing operations associated with an effective way to manage employee. The sample in this study is the entire population, ie all employees at PT BPR Artha Tunas Jaya Abadi Nganjuk totaling 47 people. The analytical method used in this research is multiple linear regression analysis. The results showed that there is a partial effect between hiring new employees, employee development, provision of job duties, the compensation of the effectiveness of the company's performance in PT. BPR Artha Tunas Jaya Abadi Nganjuk evidenced by the value of t is greater than t table at a significance level of less than 5%.While employee performance evaluation and dismissal of employees partial effect on the effectiveness of the company's performance in PT. BPR Artha Tunas Jaya Abadi Nganjuk evidenced by the t value is smaller than t table though with a significance level of less than 5%. There is influence between the accounting information system of payroll and wages on the effectiveness of the company's performance in PT. BPR Artha Tunas Jaya Abadi Nganjuk evidenced by F count larger than F table with a significance level of less than 5%.